Design and motion testing of a Multiple SMA fin driven BIUV - Zhang, Yong-hua (2021)
Fishes interact with the fluid environment using various surfaces. These multiple control surfaces work in combination to produce the thrust and the balance torques in a steady swimming, to maneuver and to position themselves accurately even in turbulent flows. These motivate us to embark on a research program designed to develop an agile biologically inspired robotic fish based on the performance of multiple fins. To accomplish this goal, a mechanical ray-like fin actuated by the shape memory alloy (SMA) is developed, which can realize the oscillating motion, the undulating motion or even the complex three dimensional motion. The basic unit is the two opposite side SMA-driven plate, namely the fin ray. As a result, a lightweight bio-inspired fin is constructed by placing radially multiple SMA fin rays. A biologically inspired underwater vehicle (BIUV) is later built using the above multiple lightweight bio-inspired fins. Two common arrangement styles of multiple fins on the BIUV are considered here: one is the posterior fin (for the oscillating motion) that is parallel to the anterior fins (for the undulating motion), another one is the posterior fin that perpendicular to the anterior fins. The kinematic modeling, the deformation modeling and the detecting of the SMA fin are made. The thrust generation is also established. Finally, an experiment is conducted to test the performance of the proposed two arrangement styles, including the comparison of the averaged propulsion velocity and the averaged thrust under certain kinematic parameters. Meanwhile, the influence of the frequency and the amplitude of the SMA fin ray on the propulsion performance is also investigated.